2020
DOI: 10.1136/gutjnl-2020-321530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resolvins on sensitisation of TRPV1 and visceral hypersensitivity in IBS

Abstract: ObjectiveResolvins (RvD1, RvD2 and RvE1) are endogenous anti-inflammatory lipid mediators that display potent analgesic properties in somatic pain by modulating transient receptor potential vanilloid 1 (TRPV1) activation. To what extent these molecules could also have a beneficial effect on TRPV1 sensitisation and visceral hypersensitivity (VHS), mechanisms involved in IBS, remains unknown.DesignThe effect of RvD1, RvD2 and RvE1 on TRPV1 activation and sensitisation by histamine or IBS supernatants was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 59 publications
0
44
0
Order By: Relevance
“…Previous controlled studies have found that patients with functional dyspepsia and IBS were highly sensitive to capsaicin or capsaicin containing foods[ 41 , 42 ]. Capsaicin could act on transient receptor potential vanilloid-1 (TRPV-1) and mediate visceral hypersensitivity[ 43 , 44 ]. A multicenter study involving Korean and Japanese populations found that, regardless of TRPV-1 genotype and Helicobacter pylori infection status, upper gastrointestinal symptoms were more common in patients who ate more spicy foods[ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous controlled studies have found that patients with functional dyspepsia and IBS were highly sensitive to capsaicin or capsaicin containing foods[ 41 , 42 ]. Capsaicin could act on transient receptor potential vanilloid-1 (TRPV-1) and mediate visceral hypersensitivity[ 43 , 44 ]. A multicenter study involving Korean and Japanese populations found that, regardless of TRPV-1 genotype and Helicobacter pylori infection status, upper gastrointestinal symptoms were more common in patients who ate more spicy foods[ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A burning sensation and/or pain can be triggered by activation of these channels by capsaicin, acidic pH, thermal stimulus, and/or inflammatory mediators. Studies have shown a positive correlation between the upregulation of TRPV1 expression and abdominal pain in colonic biopsies from patients with IBS-D [67,96]. Further, miR-199a/b has been shown to regulate TRPV1 expression, which has a major role in visceral pain induction in patients with IBS-D [26].…”
Section: Mirna Dysregulation and Visceral Hypersensitivitymentioning
confidence: 97%
“…To study the effect of GPR18 on TRPV1, neurons were incubated with 10 nM RvD2 and 30 μM O-1918, as described by Perna. 16 The F1/F0 ratio was calculated as the change in the intracellular calcium concentration.…”
Section: Calcium Imagingmentioning
confidence: 99%
“…Some studies have proven that GPR18 is expressed in the central and peripheral nervous systems; 16,18 thus, we decided to study the distribution of GPR18 in the bladder afferent pathway. Immunofluorescence analysis of PGP9.5, a nerve fibre marker, was used to confirm the existence of GPR18 in the bladder afferent pathway in normal bladder specimens.…”
Section: The Expression Of Gpr18 Was Downregulated In Rats With Cyp-induced Cystitismentioning
confidence: 99%
See 1 more Smart Citation